Epigastric symptom response to low FODMAP dietary advice compared with standard dietetic advice in individuals with functional dyspepsia. Issue 11 (12th April 2021) - Staudacher, Heidi M.; Nevin, Amy N.; Duff, Christopher; Kendall, Bradley J.; Holtmann, Gerald J.
Abstract: Background: Certain dietary constituents may provoke symptoms of functional dyspepsia (FD); however, there is an absence of dietary trials testing specific dietary interventions. Empirically derived dietary strategies and the low FODMAP diet are frequently used in practice. This study aimed to compare the effectiveness of low FODMAP dietary advice with standard dietary advice for reducing epigastric and overall gastrointestinal symptoms in individuals with FD. Methods: Data were collected from 59 consecutive eligible individuals with FD attending an initial and review outpatient dietetic consultation at Princess Alexandra Hospital. Of these, 40 received low FODMAP advice and 19 received standard dietary advice. As part of usual care, the Structured Assessment of Gastrointestinal Symptom Scale (SAGIS) was used to assess epigastric (maximum score = 28) and overall gastrointestinal symptoms (maximum score = 88). Dietary adherence data were collected, and change in symptom score and proportion of responders (defined as a ≥30% reduction in score) for epigastric and total symptoms was calculated. Key Results: Most individuals (48/59, 81%) had FD and coexisting irritable bowel syndrome. There was a greater reduction in epigastric score in those receiving low FODMAP dietary advice compared with those receiving standard advice (est. marginal mean [95% CI]: −3.6 [−4.9, −2.2] vs. −0.9 [−2.9, 1.1], p = 0.032) and total symptom score (−9.4 [−12.4, −6.4] vs. −3.3 [−7.7, 1.1] p = 0.026). A greater proportion receiving low FODMAP dietary advice were responders versus those receiving standard advice (50% vs. 16%, p = 0.012). Dietary adherence did not differ between groups ( p = 0.497). Conclusions & Inferences: The low FODMAP diet appears more effective for improving epigastric symptoms in people with FD compared with standard advice. A randomized controlled trial is required to substantiate these findings. Abstract : Low FODMAP dietary advice leads to greater epigastric symptom improvement compared with standard dietary advice in an observational study of individuals with functional dyspepsia.